Case report: The clinical utility of metagenomic next-generation sequencing in mucormycosis diagnosis caused by fatal Lichtheimia ramosa infection in pediatric neuroblastoma - Shen, Huili; Cai, Xiaodi; Liu, Jing; Yan, Gangfeng; Ye, Ying; Dong, Rui; Wu, Jufang; Li, Li; Shen, Quanli; Ma, Yutong; Ou, Qiuxiang; Shen, Meili; et al. (Frontiers in Pediatrics, 2023)
Lichtheimia ramosa (L. ramosa) is an opportunistic fungal pathogen of the order Mucorales that may result in a rare but serious mucormycosis infection. Mucormycosis could be angioinvasive, causing thrombosis and necrosis in the nose, brain, digestive tract, and respiratory tract. The infection is highly lethal, especially in immunocompromised hosts, and the incidence has been on the rise. However, due to its relatively low incidence in pediatric population and the challenges with diagnosis, the awareness and management experience for pediatric mucormycosis are extremely limited, which might lead to poor outcomes. In this study, we comprehensively reviewed the course of a fatal rhinocerebral mucormycosis case in a pediatric neuroblastoma patient receiving chemotherapy. Due to a lack of awareness of the infection, the standard care of amphotericin B treatment was delayed and not administered until the identification of L. ramosa by metagenomic next-generation sequencing (mNGS)-based pan-pathogen detection of the patient’s peripheral blood sample. We also reviewed the literature on L. ramosa infection cases reported worldwide between 2010 and 2022, with an analysis of clinical manifestation, prognosis, and epidemiological data. Our study not only highlighted the clinical value of comprehensive mNGS in rapid pathogen detection but also raised awareness of recognizing lethal fungal infection early in immunocompromised hosts including pediatric cancer patients.